Uma proposta de aprendizagem usando o cubo mágico em Malta – PB - Silva, José Vinícius do Nascimento (2015)
The aim of this work is to teach Mathematics, especially algebra and geometry, through learning algorithms and layers method for assemble the Magic Cube of Rubik 3 x 3 x 3 in an interdisciplinary way. The proposal has been applied and developed with high school students from Escola Estaudal de Ensino Fundamental e Médio Dr. Antônio Fernandes de Medeiros located in Malta Pb. In the period from June 1st, 2015 until June 5th, 2015. To achieve this goal we built through learning and hub handling applications with Geometry, Algebra, Combinatorics and Probability and issues arising from tests of Brazilian Mathematical Olympiad of Public Schools (OBMEP).